Raw material precursor, doped carbon-based material, preparation method of doped carbon-based material and supercapacitor
Doped carbon-based materials are prepared through raw material precursors composed of rice husk raw materials and alkaline compounds, which solves the problem of lower carbon yield and mass ratio capacitance of supercapacitor electrode materials, and achieves efficient and low-cost production. Excellent electrical performance.
Patent Information
- Application Number
- CN202411516613.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-20
AI Technical Summary
The existing supercapacitor electrode materials have lower carbon yield and mass ratios than capacitors, and the preparation process is complex and costly.
The raw material is prepared by using rice husk raw materials as carbon source, and the raw material precursor is prepared by ammonium chloride treatment and alkaline compounds (such as potassium hydroxide) combined with sulfur sources (such as thiourea). After pretreatment, pyrolysis treatment and etching treatment, the raw material precursor is prepared. A doped carbon-based material is obtained.
Improves carbon yield and mass specific capacitance, simplifies production process, and reduces production costs. The produced doped carbon-based materials have excellent carbon yield, nitrogen doping and sulfur doping, and have high specificity. Surface area and special pore structure.
Abstract
Description
Technical Field
[0001] The invention relates to a raw material precursor, a doped carbon-based material and a preparation method thereof, and a supercapacitor. Background Art
[0002] In today's society, supercapacitors based on double-layer charge accumulation are widely used in electronic products, medical equipment, load balancing and hybrid electric vehicles. According to the energy storage mechanism, capacitors can be divided into double-layer capacitors and pseudocapacitors. The main components of double-layer capacitors are electrodes, diaphragms and electrolytes, which affect the performance of the entire device. Electrodes provide a large number of active sites for electrolyte ions to achieve charge storage. Electrode materials are the key to determining capacitor performance. In view of this, more and more researchers are focusing on the preparation of high-performance electrode materials.
[0003] However, in the existing process of preparing supercapacitor electrode materials, not only are the procedures complicated and cumbersome, energy consumption is high, but the yield is low, which increases production costs, and the carbon yield and mass specific capacitance of the prepared electrode materials are low. Summary of the invention
[0004] The technical problem to be solved by the present invention is the low carbon yield and mass specific capacitance of the electrode material used as a supercapacitor, and provides a raw material precursor, a doped carbon-based material and a preparation method thereof, and a supercapacitor. The doped carbon-based material prepared from the raw material precursor of the present invention has excellent carbon yield and high mass specific capacitance, and the preparation method is simple and has low production cost.
[0005] The invention discloses a raw material precursor, which comprises a carbon source and an alkaline compound. The carbon source is a rice husk raw material treated with ammonium chloride.
[0006] In the present invention, the rice husk raw material is, for example, rice husk, lignin extracted from rice husk, or cellulose extracted from rice husk.
[0007] Those skilled in the art generally understand that the rice husk raw material contains silicon dioxide, and the mass percentage of silicon dioxide in the rice husk raw material is 15%-28%.
[0008] In the present invention, the mass percentage of the ammonium chloride to the rice husk raw material is preferably 5%-20%, for example, 10%.
[0009] In the present invention, the alkaline compound is preferably a metal hydroxide, such as sodium hydroxide and / or potassium hydroxide, preferably potassium hydroxide.
[0010] In the present invention, the mass ratio of the carbon source to the alkaline compound is preferably 1:(0.5-1.5).
[0011] In the present invention, preferably, the raw material precursor further comprises a sulfur source. The sulfur source in the present invention means an organic substance that can provide sulfur element.
[0012] The sulfur source is, for example, thiourea or sulfate.
[0013] The sulfate is, for example, ammonium sulfate or sodium sulfate.
[0014] In certain specific embodiments of the present invention, the mass ratio of the carbon source to the sulfur source is preferably 1:(3-7), for example, 1:5.
[0015] In the present invention, preferably, the raw material precursor does not include a phosphorus source.
[0016] In certain specific embodiments of the present invention, the raw material precursor consists of a carbon source, a sulfur source and an alkaline compound.
[0017] Preferably, the raw material precursor for the capacitor consists of rice husk raw material, ammonium chloride, potassium hydroxide and thiourea.
[0018] In the present invention, the method for preparing the carbon source preferably comprises the following steps: the rice husk raw material is soaked with an ammonium chloride solution to obtain the carbon source.
[0019] Wherein, the mass fraction of the ammonium chloride solution is preferably 5%-15%, for example, 10%.
[0020] The immersion time is preferably 3-8 hours, for example 5 hours.
[0021] The immersion temperature is, for example, room temperature, which means 20-40°C.
[0022] The solid-to-liquid ratio of the rice husk raw material to the ammonium chloride solution is preferably 1: (1-3), for example 1: 2. The solid-to-liquid ratio refers to the ratio of the mass of the rice husk raw material to the volume of the ammonium chloride solution, wherein the unit of mass is g and the unit of volume is mL.
[0023] The mixing method may be conventional in the art, such as stirring.
[0024] The stirring time is, for example, 5 hours.
[0025] It is generally understood by those skilled in the art that the impregnation treatment generally includes the steps of drying and grinding in sequence.
[0026] There is no requirement for the degree of grinding, as long as the particle size is uniform and there are no large particles with a particle size of more than 0.1 mm.
[0027] In the present invention, preferably, the method for preparing the raw material precursor comprises the following steps: mixing the carbon source, the alkaline compound and water and then drying the mixture.
[0028] Preferably, the method for preparing the raw material precursor comprises the following steps: mixing the sulfur source, the alkaline compound, the carbon source and water and then drying the mixture.
[0029] The mixing method is, for example, stirring.
[0030] The stirring time is not particularly limited, as long as the sulfur source, the alkaline compound, the carbon source and the water are uniformly mixed.
[0031] The mass ratio of the carbon source to the water is preferably 1:(20-50), more preferably 1:(30-50).
[0032] The drying temperature and time are not particularly limited, as long as the water is removed.
[0033] The present invention also discloses a method for preparing a doped carbon-based material, which comprises the following steps: sequentially subjecting the raw material precursor to pretreatment, pyrolysis treatment and etching treatment to obtain the doped carbon-based material;
[0034] The temperature of the pretreatment insulation stage is 400-500°C.
[0035] In the present invention, a pretreatment step is performed before the pyrolysis treatment, so that the alkaline compound can be evenly distributed, thereby improving the uniformity of the pore size of the doped carbon-based material.
[0036] In the present invention, preferably, the pretreatment further includes drying and grinding the raw material precursor in sequence.
[0037] Wherein, the temperature of the drying treatment is preferably 80-100°C.
[0038] In the present invention, the pretreatment and the pyrolysis treatment are both performed in a tube furnace, for example.
[0039] In certain specific embodiments of the present invention, the pretreatment and the pyrolysis treatment are both carried out under a nitrogen atmosphere.
[0040] In the present invention, preferably, the pretreatment further includes a heating stage before the heat preservation stage, and the heating rate of the heating stage is 3-8°C / min, for example, 5°C / min.
[0041] In the present invention, preferably, the temperature of the pretreatment heat preservation stage is 420-480°C, for example, 450°C.
[0042] In the present invention, preferably, the time of the heat preservation stage of the pretreatment is 0.3-2h, for example, 0.5h.
[0043] In the present invention, preferably, the temperature of the pyrolysis treatment is 800-850°C.
[0044] In the present invention, preferably, the pyrolysis treatment time is 1-5 hours, for example, 2 hours.
[0045] Those skilled in the art generally understand that after the pyrolysis treatment, the temperature is generally lowered to room temperature under an inert gas atmosphere.
[0046] In the present invention, preferably, after the pyrolysis treatment and before the etching treatment, an acid wash treatment is further included. The acid wash treatment can effectively remove the metal ions remaining in the doped carbon-based material.
[0047] The pickling treatment is performed using hydrochloric acid, for example, and the concentration of the hydrochloric acid is, for example, 0.5 mol / L.
[0048] Wherein, after the pyrolysis treatment and before the acid washing treatment, it is preferred to further include the steps of water washing and filtering.
[0049] The water washing, for example, comprises the following steps: mixing the solid obtained after the pyrolysis treatment with water.
[0050] The mass ratio of the solid obtained after the pyrolysis treatment to the water is, for example, 1:(80-100).
[0051] The mixing is performed by stirring, for example, and the stirring time is, for example, 30 minutes.
[0052] The filtration is performed, for example, using qualitative filter paper.
[0053] In certain specific embodiments of the present invention, the acid washing treatment further includes water washing and drying steps.
[0054] There is no particular limitation on the time of washing with water, and washing with water until the mixture becomes neutral is sufficient.
[0055] Wherein, the drying temperature is preferably 90-100°C.
[0056] Wherein, the drying time is preferably 12-24 hours.
[0057] The drying device is, for example, a vacuum drying oven.
[0058] In the present invention, the etchant used in the etching process is, for example, HF solution.
[0059] The mass fraction of the HF solution is preferably 5wt%-15wt%, for example, 10wt%.
[0060] In the present invention, the etching treatment time is preferably 1-3 hours, for example 2 hours.
[0061] In the present invention, the temperature of the etching process is, for example, 20-40°C.
[0062] In certain specific embodiments of the present invention, the etching process further includes steps of rinsing and drying.
[0063] There is no particular limitation on the time of washing with water, and washing with water until the mixture becomes neutral is sufficient.
[0064] Wherein, the drying temperature is preferably 80-100°C.
[0065] The drying time is, for example, 12 hours.
[0066] In the present invention, preferably, the pore size D50 of the doped carbon-based material is 1-3 nm, for example, 1.9 nm, 2.3 nm or 3.1 nm.
[0067] In the present invention, preferably, the nitrogen doping amount of the doped carbon-based material is 7wt%-11wt%, for example, 7.5wt%, 9.5wt% or 10.4wt%, wherein the nitrogen doping amount means the mass content of nitrogen element in the doped carbon-based material.
[0068] In the present invention, preferably, the sulfur doping amount of the doped carbon-based material is 5wt%-8wt%, for example, 6.3wt%, 6.5wt%, 7wt% or 7.1wt%, wherein the sulfur doping amount means the mass content of sulfur element in the doped carbon-based material.
[0069] In the present invention, preferably, the specific surface area of the doped carbon-based material is 450 m 2 / g or more, preferably 670-1000m 2 / g, for example, 675m 2 / g or 732m 2 / g.
[0070] In the present invention, preferably, the carbon yield of the doped carbon-based material is preferably 45% or more, more preferably 45%-55%, for example, 48.3%, 49.2%, 51%, 51.3%, 51.5% or 51.7%. The carbon yield in the present invention is calculated as follows: mass of the doped carbon-based material / mass of the carbon source.
[0071] The invention also discloses a doped carbon-based material prepared by the preparation method.
[0072] The invention also discloses a supercapacitor, which comprises the doped carbon-based material.
[0073] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0074] The reagents and raw materials used in the present invention are commercially available.
[0075] The positive and progressive effects of the present invention are:
[0076] The carbon source of the raw material precursor of the present invention is rice husk as raw material, ammonium chloride is introduced, and an alkaline compound is combined, which can not only introduce heteroatom nitrogen, but also greatly improve the carbon yield. The process of preparing doped carbon-based materials using the raw material precursor of the present invention can simplify the production process and reduce production costs. The doped carbon-based material prepared by the present invention has excellent carbon yield, nitrogen doping amount and sulfur doping amount, and has a special pore structure and a high specific surface area. It can be prepared into a supercapacitor with excellent mass specific capacitance. DETAILED DESCRIPTION
[0077] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0078] The rice husks used in the following examples and comparative examples were purchased from Guchuan Rice Industry in Yushu City, wherein the mass percentage of silicon dioxide in the rice husks was 20%±2%.
[0079] Example 1
[0080] The doped carbon-based material of Example 1 is prepared by the following steps:
[0081] S1: The purchased rice husks are screened, cleaned, washed, dried, and crushed in sequence to obtain rice husk raw materials for later use; wherein, the degree of crushing is not required, and the hard outer shell of the rice husk can be broken;
[0082] S2: 10 g of the rice husk and 20 mL of a 10 wt% ammonium chloride solution are immersed at room temperature for 5 h, and then dried and ground to obtain a carbon source in which ammonium chloride accounts for 20% of the mass percentage of the rice husk raw material; wherein the degree of grinding is not required, as long as the particle size is uniform and there is no large particle with a particle size of more than 0.1 mm;
[0083] S3: Take 2g of carbon source, 1g of KOH, 10g of thiourea and 60g of deionized water, stir at room temperature for 5h, and obtain a raw material precursor for capacitors after drying; wherein the drying temperature is 89-90°C and the drying time is 12h to remove water.
[0084] S4: Grind the raw material precursor obtained in step S3 evenly and place it in a tube furnace. In a nitrogen atmosphere, heat it to 450°C at a heating rate of 5°C / min for pretreatment for 0.5h to completely melt KOH; then heat it to 800°C for 2h of pyrolysis treatment; then cool it to room temperature in a nitrogen atmosphere to obtain a black solid; mix the obtained black solid with deionized water at a mass ratio of 1:100, stir for 30min, filter it with qualitative filter paper, wash the filter cake with 0.5mol / L dilute hydrochloric acid to remove the residual metal ions in the sample, wash it with deionized water to neutrality, and dry it in a vacuum drying oven at 100°C for 12h; then perform etching treatment at room temperature for 2h, the etching agent used in the etching treatment is 10wt% HF solution, wash the sample with deionized water to neutrality after etching treatment, and dry it at 100°C for 12h to obtain a finished doped carbon-based material. The doped carbon-based material has a high degree of pore size uniformity.
[0085] Example 2
[0086] The doped carbon-based material of Example 2 is prepared by the following steps: 6 g of thiourea is used in S3, and the rest is consistent with Example 1. The pore size uniformity of the doped carbon-based material is high.
[0087] Example 3
[0088] The doped carbon-based material of Example 3 is prepared by the following steps: 14 g of thiourea is used in S3, and the rest is consistent with Example 1. The pore size uniformity of the doped carbon-based material is high.
[0089] Example 4
[0090] The doped carbon-based material of Example 4 is prepared by the following steps: 6 g of thiourea in S3, pyrolysis treatment at 850° C. for 2 h in S4, and the rest is the same as in Example 1. The pore size uniformity of the doped carbon-based material is high.
[0091] Example 5
[0092] The doped carbon-based material of Example 5 is prepared by the following steps: In S4, the temperature is raised to 850° C. for 2 h of pyrolysis treatment, and the rest is consistent with Example 1. The pore size uniformity of the doped carbon-based material is high.
[0093] Example 6
[0094] The doped carbon-based material of Example 6 is prepared by the following steps: 14 g of thiourea in S3, heating to 850° C. for 2 h of pyrolysis in S4, and the rest is the same as in Example 1. The pore size uniformity of the doped carbon-based material is high.
[0095] Example 7
[0096] The doped carbon-based material of Example 7 is prepared by the following steps: KOH in S3 is replaced by potassium carbonate, and the rest is the same as in Example 1. The pore size uniformity of the doped carbon-based material is high.
[0097] Comparative Example 1
[0098] The doped carbon-based material of Comparative Example 1 is prepared by the following steps: S3 does not contain KOH, and the rest is consistent with Example 2. The pore size distribution of the doped carbon-based material is uneven, and the micropores account for a small proportion, and the specific surface area is low.
[0099] Comparative Example 2
[0100] The doped carbon-based material of Comparative Example 2 was prepared by the following steps: in S2, the rice husk raw material was not impregnated with the ammonium chloride solution at room temperature, and the rest was consistent with Example 1. The pore size distribution of the doped carbon-based material was relatively uniform, but the carbon yield was low.
[0101] Comparative Example 3
[0102] The doped carbon-based material of Comparative Example 3 was prepared by the following steps:
[0103] S1: The purchased rice husks are screened, cleaned, washed, dried, and crushed in sequence to obtain rice husk raw materials for later use; wherein, the degree of crushing is not required, and the hard outer shell of the rice husk can be broken;
[0104] S2: Grind the rice husks obtained in step S1 uniformly and place them in a tube furnace. In a nitrogen atmosphere, heat them to 450°C at a heating rate of 5°C / min for pretreatment; then heat them to 800°C for 2h of pyrolysis treatment; then cool them to room temperature in a nitrogen atmosphere to obtain a black solid; mix the obtained black solid with deionized water at a mass ratio of 1:100, stir for 30min, filter with qualitative filter paper, wash the filter cake with 0.5mol / L dilute hydrochloric acid to remove the metal ions remaining in the sample, wash with deionized water to neutrality, and dry in a vacuum drying oven at 100°C for 12h; then perform etching treatment, the etching agent used in the etching treatment is 10wt% HF solution, wash the sample with deionized water to neutrality after etching treatment, and dry it at 100°C for 12h to obtain a finished doped carbon-based material. The doped carbon-based material has uneven pore size, low specific surface area, and low carbon yield.
[0105] Effect Example 1
[0106] The following tests were performed on Examples 1-6 and Comparative Examples 1-3:
[0107] 1. Carbon yield test: The mass of the raw rice husk and the mass of the prepared doped carbon-based material were weighed respectively. The carbon yield was calculated as follows: the mass of the doped carbon-based material / the mass of the rice husk raw material treated with ammonium chloride.
[0108] 2. Pore diameter D50 and specific surface area test: Using the ASAP2020 instrument produced by Micromeritics, USA, under the conditions of nitrogen adsorption and desorption, the Brunauer-Emmet-Teller (BET) model was used to calculate the specific surface area of the doped carbon-based material, and the Density Functional Theory (DFT) model was used to calculate the pore diameter D50 of the doped carbon-based material.
[0109] 3. Nitrogen doping amount and sulfur doping amount test: The Vario EL Cube instrument of Elementar Company of Germany is used to perform elemental analysis on the doped carbon-based materials, and the mass content of nitrogen and the mass content of sulfur in the doped carbon-based materials are calculated respectively, that is, the nitrogen doping amount and the sulfur doping amount.
[0110] 4. Determination of mass specific capacitance: The prepared doped carbon-based material, conductive agent (conductive acetylene black) and binder (polytetrafluoroethylene) were stirred, heated and evaporated in ethanol at a mass ratio of 85:10:5, and ground to obtain a uniform slurry, which was rolled into sheets and cut into 1cm*1cm squares, and then pressed onto nickel foam to make a working electrode. The saturated calomel electrode and platinum electrode were used as reference electrode and counter electrode, respectively. The electrodes were subjected to constant current charge and discharge tests using an electrochemical workstation (model CHI 660) with a three-electrode system at room temperature, with a voltage range of -1~0V and a current density of 0.5A / g.
[0111] The mass specific capacitance Cg (unit: F / g) of the working electrode is calculated by the following formula: Cg=(I*Δt) / (m*ΔV), where I is the discharge current (A), Δt is the discharge time (s), ΔV is the potential difference during the discharge process (V), and m is the mass of the active material in a single electrode (g).
[0112] The above test results are listed in Table 1 below:
[0113] Table 1
[0114] Carbon yield Aperture D50 (nm) Nitrogen doping amount (wt%) Sulfur doping amount (wt%) <![CDATA[Specific surface area (m 2 / g)]]> Mass specific capacitance (F / g) Example 1 51% 2.3 9.5 7.1 675 234 Example 2 51.7% 1.9 7.5 6.3 732 208 Example 3 48.3% 3.1 10.4 6.5 459 170 Example 4 51.3% 2.1 8.1 6.6 720 190 Example 5 51.5% 2.0 6.9 5.9 755 194 Example 6 49.2% 2.8 9.0 6.4 523 183 Comparative Example 1 38% 3.3 5.1 4 514 168 Comparative Example 2 23.2% 2.9 4.5 5.3 570 164 Comparative Example 3 31.90% 4.5 0 0 350 141
[0115] According to the results in Table 1, the carbon yield of the carbon source in the doped carbon-based materials prepared in Examples 1-6 is above 45%, and the highest can reach 51.7%, indicating that it has excellent carbon yield. The pore size D50 of the doped carbon-based materials is 1.9-3.1nm, and the surface area is 459-732m 2 / g, nitrogen doping amount is 7.5wt%-10.4wt%, and sulfur doping amount is 6.3wt%-7.1wt%, indicating that it has high sulfur and high nitrogen doping. The results of electrical performance testing of its doped carbon-based material prepared into electrodes show that its mass specific capacitance can reach more than 170F / g, indicating that it has excellent supercapacitor performance.
[0116] Compared with Example 2 and Comparative Example 1, S3 does not contain KOH, resulting in a carbon yield of its carbon source reduced to 38%, a significant decrease in nitrogen doping and sulfur doping amounts, and a decrease in mass specific capacitance from 208 F / g to 168 F / g, indicating that the absence of alkaline compounds in the raw material precursor is not conducive to the nitrogen doping amount, sulfur doping amount and carbon yield.
[0117] Compared with Example 1, in Comparative Example 2, the rice husk raw material was not impregnated with the ammonium chloride solution at room temperature, resulting in a significant decrease in its carbon yield, nitrogen doping amount and sulfur doping amount, indicating that the addition of ammonium chloride has a great effect on improving the carbon yield, nitrogen doping amount and sulfur doping amount.
[0118] Compared with Example 1, in Comparative Example 3, the raw material precursor does not contain alkaline compounds, the carbon source is rice husk raw material that has not been treated with ammonium chloride, there is no nitrogen doping and sulfur doping, and the carbon yield and mass specific capacitance are both worse.
Claims
1. A raw material precursor, It is characterized in that The invention comprises a carbon source and an alkaline compound, wherein the carbon source is a rice husk raw material treated with ammonium chloride.
2. The raw material precursor according to claim 1, It is characterized in that The raw material precursor meets one or more of the following conditions: (1) The mass percentage of the ammonium chloride in the rice husk raw material is 5%-20%, for example, 10%; (2) The alkaline compound is a metal hydroxide, such as sodium hydroxide and / or potassium hydroxide, preferably potassium hydroxide; (3) The mass ratio of the carbon source to the alkaline compound is 1:(0.5-1.5); (4) The raw material precursor further includes a sulfur source; wherein the sulfur source is, for example, thiourea or sulfate; wherein the sulfate is, for example, ammonium sulfate or sodium sulfate; Wherein, the mass ratio of the carbon source to the sulfur source is preferably 1:(3-7), for example, 1:5; (5) The raw material precursor does not include a phosphorus source.
3. The raw material precursor according to claim 1 or 2, It is characterized in that The raw material precursor meets one or more of the following conditions: (1) The method for preparing the carbon source comprises the following steps: soaking the rice husk raw material with an ammonium chloride solution to obtain the carbon source; Wherein, the mass fraction of the ammonium chloride solution is preferably 5%-15%, for example, 10%; The immersion time is preferably 3-8 hours, for example 5 hours. The solid-liquid ratio of the rice husk raw material to the ammonium chloride solution is preferably 1: (1-3), for example 1: 2; wherein the solid-liquid ratio means the ratio of the mass of the rice husk raw material to the volume of the ammonium chloride solution, the unit of mass is g, and the unit of volume is mL; (2) The method for preparing the raw material precursor comprises the following steps: mixing the carbon source, the alkaline compound and water and drying the mixture; The method for preparing the raw material precursor preferably comprises the following steps: mixing the sulfur source, the alkaline compound, the carbon source and water and drying the mixture; The mass ratio of the carbon source to the water is preferably 1:(20-50), more preferably 1:(30-50).
4. A method for preparing a doped carbon-based material, It is characterized in that The method comprises the following steps: sequentially subjecting the raw material precursor according to any one of claims 1 to 3 to pretreatment, pyrolysis treatment and etching treatment to obtain a doped carbon-based material; The temperature of the pretreatment insulation stage is 400-500°C.
5. The method for preparing the doped carbon-based material according to claim 4, It is characterized in that It meets one or more of the following conditions: (1) Before the pretreatment, the raw material precursor is dried and ground in sequence; wherein the drying temperature is preferably 80-100°C; (2) The pretreatment and the pyrolysis treatment are both carried out in a tubular furnace; (3) The pretreatment further includes a heating stage before the heat preservation stage, and the heating rate of the heating stage is 3-8°C / min, for example, 5°C / min; (4) The temperature of the pretreatment insulation stage is 420-480°C, for example, 450°C; (5) The pretreatment heat preservation stage lasts for 0.3-2 hours, for example, 0.5 hours; (6) The temperature of the pyrolysis treatment is 800-850°C; (7) The pyrolysis treatment time is 1-5 hours, for example, 2 hours.
6. The method for preparing the doped carbon-based material according to claim 4, It is characterized in that After the pyrolysis treatment and before the etching treatment, it also includes an acid pickling treatment; The pickling treatment is performed, for example, with hydrochloric acid; wherein the concentration of the hydrochloric acid is, for example, 0.5 mol / L; Wherein, after the pyrolysis treatment and before the acid washing treatment, it is preferred to further include the steps of water washing and filtering; The water washing, for example, comprises the following steps: mixing the solid obtained after the pyrolysis treatment with water; wherein the mass ratio of the solid obtained after the pyrolysis treatment to the water is, for example, 1:(80-100); wherein the mixing is, for example, performed by stirring, wherein the stirring time is, for example, 30 minutes; Wherein, the filtering is performed, for example, using qualitative filter paper; The acid pickling treatment may further include water washing and drying steps in sequence; the drying temperature may be preferably 90-100°C; the drying time may be preferably 12-24h; the drying device may be a vacuum drying oven, for example.
7. The method for preparing the doped carbon-based material according to claim 4, It is characterized in that It meets one or more of the following conditions: (1) The etchant used in the etching process is HF solution; wherein the mass fraction of the HF solution is preferably 5wt%-15wt%, for example, 10wt%; (2) The etching treatment time is preferably 1-3 hours, for example 2 hours; (3) The temperature of the etching process is 20-40°C; (4) After the etching process, the steps of water washing and drying are sequentially included; wherein the drying temperature is preferably 80-100° C.; wherein the drying time is, for example, 12 hours.
8. The method for preparing the doped carbon-based material according to claim 4, It is characterized in that It meets one or more of the following conditions: (1) The pore size D50 of the doped carbon-based material is 1-3 nm, for example, 1.9 nm, 2.3 nm or 3.1 nm; (2) The nitrogen doping amount of the doped carbon-based material is 7wt%-11wt%, for example, 7.5wt%, 9.5wt% or 10.4wt%; (3) The sulfur doping amount of the doped carbon-based material is 5wt%-8wt%, for example, 6.3wt%, 6.5wt%, 7wt% or 7.1wt%; (4) The specific surface area of the doped carbon-based material is 450 m 2 / g or more, preferably 670-1000m 2 / g, for example, 675m 2 / g or 732m 2 / g; (5) The carbon yield of the doped carbon-based material is greater than 45%, more preferably 45%-55%, for example, 48.3%, 49.2%, 51%, 51.3%, 51.5% or 51.7%.
9. A doped carbon-based material obtained by the method for preparing a doped carbon-based material according to any one of claims 4 to 8.
10. A supercapacitor, It is characterized in that It comprises the doped carbon-based material as claimed in claim 9.
